Origin of ultraweak fluorescence of 8-hydroxyquinoline in water: photoinduced ultrafast proton transfer. Issue 12 (25th January 2016) - Park, Sun-Young; Ghosh, Prasun; Park, Sung O.; Lee, Young Min; Kwak, Sang Kyu; Kwon, Oh-Hoon
Abstract : Ultrafast excited-state proton transfer of 8-hydroxuquinoline to produce short-lived its tautomeric form causes immensely attenuated fluorescence in water. Abstract : 8-Hydroxyquinoline (8-HQ), commonly known as oxine, is the most popular among the hydroxyquinolines due to its excellence in complex formation with metal ions and with a wide spectrum of pharmacological applications. 8-HQ and many of its derivatives are fluorogenic ligands when complexed with metal ions. Thus they are regularly used for detection, separation, and quantitative analysis of metal ions as well. For example when chelated with aluminum, the coordinated complex exhibits strong visible emission, which is applicable for the fabrication of organic light-emitting diodes. Although metal complexes with 8-HQ and its derivatives are fluorescent promising wide applications, the ligand itself, 8-HQ, is surprisingly a very weak fluorophore in most of the media, because of its short lifetime in the excited state. To address the nature of ultrashort-lived 8-HQ in the excited sate, we study its photochemical and photophysical processes in acidic, basic, and neutral aqueous media. Our results show that 8-HQ as well as its protonated and deprotonated forms, undergoes ultrafast excited-state proton transfer within femto-to-picoseconds to produce a tautomer as a product, the lifetime of which is also ultrashort. This can give a clue as to why metal complexes of 8-HQ generally show strong fluorescence whereas 8-HQ itself is rarely fluorescent in aqueous solutions; when 8-HQ binds to metal cations, the ligand is in the deprotonated (anionic) form, which cannot undergo the ultrafast proton transfer without generating the short-lived dark product, but survives much longer to tens of nanoseconds to "turn on" fluorescence.